2016
DOI: 10.1111/1748-8583.12097
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the black box: understanding the relationship between strategy, HRM practices, innovation and organizational performance

Abstract: The links between HRM practices and organizational performance have received considerable research attention as significant contributors to sustained competitive advantage. However, the processes that link HRM practices and organizational performance are not fully understood. This study examines the relationships between skill-enhancing, motivation-enhancing and opportunity-enhancing bundles of practices, innovation and organizational performance, and looks at the mediating effect of innovation over time at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
196
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(217 citation statements)
references
References 54 publications
14
196
1
6
Order By: Relevance
“…Research about human capital predominantly considered the role of systems of human capital (Chowhan, 2016). Such a system consists of several components, which have been considered all together as having an impact on firm performance.…”
Section: Human Capital and Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…Research about human capital predominantly considered the role of systems of human capital (Chowhan, 2016). Such a system consists of several components, which have been considered all together as having an impact on firm performance.…”
Section: Human Capital and Innovationmentioning
confidence: 99%
“…Previous studies pointed out that strategic activities have an effect on human capital and performance (Chowhan, 2016). Therefore, we control for two strategic activities, namely conducting research and development and if the firm is active in the international market by exporting.…”
Section: Foreign Presence or Foreign Ownedmentioning
confidence: 99%
See 1 more Smart Citation
“…HPWS refer to a group of separate but interconnected HR management practices, including comprehensive recruitment and selection procedures, incentive compensation and performance management systems, and extensive employee involvement and training, which are designed to enhance employee and firm performance outcomes through improving workforce competence, attitudes, and motivation (Huselid, 1995). Previous studies have shown that HPWS can improve job satisfaction and organizational commitment (Takeuchi, Chen, & Lepak, 2009;Heffernan & Dundon, 2016), positively correlate with employee in-role behavior and organizational citizenship behavior (Miao, Zhou, Liu, & Li, 2013;Yan & Chen, 2016;Zhang & Long, 2017), and enhance the firm-level performance (Chowhan, 2016;Zhang & Long, 2017). Recognized by formal reward systems, in-role behavior is part of the requirements as described in job description, while organizational citizenship behavior (OCB) is "individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organization" (Organ, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…La GRRHH como área de conocimiento se encarga del estudio de las relaciones laborales, de la forma en que los individuos son gestionados en el trabajo (Paauwe, 2009) y de su influencia en el rendimiento de la empresa (Bowen y Ostroff, 2004;Chowhan, 2016). En un sentido amplio, la GRRHH se relaciona con la selección de políticas, prácticas y estructuras para gestionar a los empleados (Sisson, 1990;Boxall y Purcell, 2003), estando tradicionalmente orientada a las prácticas de RRHH individuales (Becker y Huselid, 2006;Jiang et al, 2012b).…”
Section: La Gestión De Los Recursos Humanosunclassified